Improving Cytokines and HDL in Diabetic Wistar Rats by Using Combination of Curcumin and Metformin - Dinanti, Fathia Kesuma; Mulyani, Sri Priyantini; Chodidjah, Chodidjah (Mutiara Medika: Jurnal Kedokteran dan Kesehatan, 2023)
In type 2 diabetes mellitus, lipid profile is often found in the form of high-density lipoprotein (HDL) decrease. TNFa and IL-6 are proinflammatory cytokines that are elevated in the blood in many patients with diabetes mellitus. Turmeric is one of the natural ingredients that have anti-cholesterol and anti-inflammatory effects through the work of its active substance, curcumin. This study aims to evaluate the effect of turmeric extract combined with metformin on HDL, TNFa, and IL-6 levels in diabetic rats. Twenty-four Wistar rats were injected intraperitoneally with streptozotocin and niacinamide. The diabetic rats were divided into control, metformin, turmeric, and combination groups. The dose of metformin and turmeric were given, respectively, 45mg/KgBW/day and 200 mg/KgBW/day. At the same time, the combo group was given a half dose of each. Blood serum was taken to examine the HDL, IL-6, and TNFa levels. The levels of HDL, IL-6, and TNFain diabetic rats that received the combination of metformin and turmeric extract (p0.05) were the best among all the groups. It indicated that the combination of metformin and turmeric was better in increasing HDL and reducing IL-6 and TNFa levels better than metformin or turmeric extract alone.